2008
DOI: 10.1177/1933719107309647
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effect of Phorbol Ester PMA on PTGS2 and PGDH mRNA Expression in Human Chorion Trophoblast Cells

Abstract: Prostaglandins (PGs) induce the mechanism of labor in humans. The enzymes responsible for PG synthesis and metabolism are prostaglandin-endoperoxide synthase 2 (PTGS2) and 15-hydroxyprostaglandin dehydrogenase (PGDH). In human chorion trophoblast cells, calcium ionophore A23187 upregulates PTGS2 and downregulates PGDH protein and mRNA. The authors hypothesize that this regulation requires activation of protein kinase C (PKC) and mitogen-activated protein kinases (MAPKs). Human chorion trophoblasts were incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…For example, cAMP generally stimulates PGDH expression, but cAMP decreased PGDH expression and activity in human trophoblast cells (Lennon et al 1999). Though PMA generally increases PGDH expression (Tai et al 2006), the ability of PMA to decrease PGDH expression has been reported (Casciani et al 2008). These examples provide precedent for the regulation of PGDH observed in the present study, where cAMP/Epac activation increased, and PLC/PKC activity decreased, PGDH mRNA, protein, and activity.…”
Section: 0 Discussionmentioning
confidence: 99%
“…For example, cAMP generally stimulates PGDH expression, but cAMP decreased PGDH expression and activity in human trophoblast cells (Lennon et al 1999). Though PMA generally increases PGDH expression (Tai et al 2006), the ability of PMA to decrease PGDH expression has been reported (Casciani et al 2008). These examples provide precedent for the regulation of PGDH observed in the present study, where cAMP/Epac activation increased, and PLC/PKC activity decreased, PGDH mRNA, protein, and activity.…”
Section: 0 Discussionmentioning
confidence: 99%
“…After seeding, MSCs attach and spread on PU films. Local calcium near the leading edge of the cell can activate cell migration while the calcium influx can stimulate NF‐κB pathway and PTGS2 expression . The NF‐κB pathway has been reported to modulate the aggregate formation of neural stem cells .…”
Section: Resultsmentioning
confidence: 99%
“…[2,17,20] Traditionally, it is known that fetal membranes produce cyclooxygenase-2 and prostaglandins that contribute to membrane weakening and rupture at term. [59][60][61][62][63][64] Recent studies suggest that fetal membranes from both humans and mice undergo a reactive oxygen species induced (due to intrauterine oxidative stress at term), telomere-dependent, activation of p38 mitogen-activated protein kinase (p38MAPK). [24,31,[65][66][67][68] p38MAPK is a stress signaler that can contribute to various cell fates.…”
Section: Fetal Membrane Function During Gestation and Parturitionmentioning
confidence: 99%